2023
DOI: 10.1021/acsaelm.2c01252
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal–Hydrogel Biosensor for Behavior and Sweat Monitoring

Abstract: Flexible electronic devices have been widely investigated by researchers over the last few years. However, due to poor biocompatibility and nondegradability in vivo, there are currently no sufficient flexible electronics that can be implanted in the body to monitor heart health in situ. Gelatin methacryloyl (GelMA)a gelatin-based hydrogel with a porous interioris widely used in bioengineering given its unique biocompatibility. Liquid metal (GaInSn alloy, 68.5 wt % Ga, 21.5 wt % In, and 10.0 wt % Sn) has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…As shown in Figure a, the channel acts as a conductive circuit and serves as packaging to prevent leakage . Researchers have also tried to combine a liquid metal with other materials such as sponges, , polymers, ,, and hydrogels, ,,, as a composite as shown in Figure b–e. By mixing a liquid metal with other low-modulus polymers (Figure c) or hydrogel (Figure e), , the phenomenon of liquid flow is eliminated while maintaining fluidity at the microscopic level, resulting in a material with an electrical stability.…”
Section: Strain-compliance With Lowering Effective Moduli Of Material...mentioning
confidence: 99%
“…As shown in Figure a, the channel acts as a conductive circuit and serves as packaging to prevent leakage . Researchers have also tried to combine a liquid metal with other materials such as sponges, , polymers, ,, and hydrogels, ,,, as a composite as shown in Figure b–e. By mixing a liquid metal with other low-modulus polymers (Figure c) or hydrogel (Figure e), , the phenomenon of liquid flow is eliminated while maintaining fluidity at the microscopic level, resulting in a material with an electrical stability.…”
Section: Strain-compliance With Lowering Effective Moduli Of Material...mentioning
confidence: 99%
“…Cu 能提高结构稳定性和空气稳定性, 这可能与 Cu 掺杂能导致 Na 层收缩有关 [46] 。 另外 Cu 还具有一定电 化学活性,因此以 Cu/Fe/Mn 为基础的 O3 相钠离子层 [96] 。该正极与硬碳负极组装的 全电池的能量密度为 210 Wh/kg, 能量效率高达 90%, 在 6 C 的高倍率下能保持初始容量的 74%。更多研究 也证实 Cu 取代能降低 Mn 3+ 含量,抑制 Mn 3+/4+ 的电化 学活性,并可能诱导更多无活性的 Mn 2+ 形成,提升材 料的循环稳定性(图 8c) [97] 。 Cu/Fe/Mn 体系中的阳离子相对含量也会影响材 料的性能。更低的 Mn 初始价态对应更高的正极比容 量;Fe 含量越高对应更高的平均电压;而适量的 Cu 则有利于更高的倍率性能和循环稳定性 (图 8d) 。 另外 此研究还发现, Mn/Fe 的含量比值会对 Mn 3+/4+ 和 Fe 3+/4+ 耦的氧化还原电位造成影响,这可能与超电荷相互作 用及 J-T 效应有关 [98] 。除过渡金属外,碱金属离子含 量也会影响材料的性能。Lu [99] 等通过合成实验和理论 计算探究了 Na 含量对 O3-Nax[Cu0.18Fe0.3Mn0.52]O2 的 影响。研究结果证实,Na 含量为 0.8 的 Na0.8-CFM 处 在 O3/P3 相的临界值,其相变所需能量较小,O3 相晶 格演化和相变更温和,材料的能量效率显著提高(图 8e) 。不过需要指出的是,Mn 3+/4+ 较低的反应电位会导 致较低的能量密度和异常的初始库伦效率。性能改善 方面,Hu [100] 等 在 其 报 道 过 的 O3-Na0. 9…”
Section: F O R R E V I E W O N L Yunclassified
“…It has been shown that the signal intensity detected by the LM–hydrogel electrodes increased with the increasing concentrations of NaCl, d -lactic acid, and glucose, providing reliability and durability. 163 Electrodes based on LM–hydrogel composites exhibit multifunctionality and are expected to provide a unique platform for practical medical applications of noninvasive health monitoring devices.…”
Section: Applications Of Lm–hydrogel Compositesmentioning
confidence: 99%